Financial insecurity in ageing population - Sinnappan Alphonce, Yugeetha Alphonce; Sinitharan, Yashini; Kethiravan, Dhivashini; Karunanithy, Kavitha; Gunentharan, Anbarasi; Rosnon, Mohd Roslan; Abdul Razak, Muhammad Afiq; Kunasekaran, Puvaneswaran; Ibrahim, Rahimah (Human Resources Management Academic Research Society (HRMARS), 2024)
Financial insecurity in the ageing population is significantly growing worldwide with multifaceted implications for individuals and society. According to the Revision of the World Population Prospects, the global population of adults over 60 is projected to reach 2.1 billion by 2050. The main causes are decreased fertility rates, increased life expectancy, demographic shifts and delayed childbirth. This paper explores the key issues of financial insecurity in the ageing population, which include food insecurity, physical health and disability, and economic instability. The analysis highlights how these effects intertwine, exacerbating the financial vulnerability of older adults. All the key factors were gathered from various local and academic journals with high-impact factors, and secondary data were also analysed to understand the issue further. Addressing financial insecurity requires comprehensive strategies such as monitoring government social security systems, providing social protection, and improving the financial literacy of the ageing community through social work and government intervention programmes. By examining the root causes and proposing actionable solutions, this paper aims to contribute to the policies and initiatives that can secure financial stability for the ageing population.